The Numerical Simulation of Hard Rocks for Tunnelling Purposes at Great Depths: A Comparison between the Hybrid FDEM Method and Continuous Techniques - Nicholas Vlachopoulos; Ioannis Vazaios (Advances in Civil Engineering)
Tunnelling processes lead to stress changes surrounding an underground opening resulting in the disturbance and potential damage of the surrounding ground. Especially, when it comes to hard rocks at great depths, the rockmass is more likely to respond in a brittle manner during the excavation. Continuum numerical modelling and discontinuum techniques have been employed in order to capture the complex nature of fracture initiation and propagation at low-confinement conditions surrounding an underground opening. In the present study, the hybrid finite-discrete element method (FDEM) is used and compared to techniques using the finite element method (FEM), in order to investigate the efficiency of these methods in simulating brittle fracturing. The numerical models are calibrated based on data and observations from the Underground Research Laboratory (URL) Test Tunnel, located in Manitoba, Canada. Following the comparison of these models, additional analyses are performed by integrating discrete fracture network (DFN) geometries in order to examine the effect of the explicit simulation of joints in brittle rockmasses. The results show that in both cases, the FDEM method is more capable of capturing the highly damaged zone (HDZ) and the excavation damaged zone (EDZ) compared to results of continuum numerical techniques in such excavations.